Condition assessment on hydropower dam based on simulation approach: A review - Salwa A.; Zawawi M.H.; Ramli M.Z.; Zahari N.M.; Saleha A.; Hassan N.H.; Radzi M.R.M.; Sidek L.M.; Muda Z.C. (American Institute of Physics Inc., 2023)
The understanding of dam structure condition under the static and dynamic should be aware as to fulfils the criteria of safety to the public. Furthermore, it is crucial to understand the parameter of the condition assessment of hydropower dam. Sliding failure, overturning failure, concrete deterioration, concrete distress, internal failure and foundation failure are the parameter induced to damage the dam stability. However, due to some areas on dam structure are difficult to be assessed such as its penstock and spillway, development condition assessment rating on structural condition for hydropower dam based on fluid-structure interaction (FSI) simulation approach is vital since it is impossible to stop the dam operation as it is needed in generating electricity. The present study aimed is to summarize the collection of various papers that related to dam analysis as to develop the condition assessment rating on structural condition for hydropower dam based on fluid-structure interaction (FSI) simulation approach. 2018 Author(s).